2022
DOI: 10.1007/s00423-022-02501-z
|View full text |Cite
|
Sign up to set email alerts
|

Single anastomosis duodenal-ileal bypass with sleeve gastrectomy (SADI-S): experience from a high-bariatric volume center

Abstract: Purpose Biliopancreatic diversion with duodenal switch and single anastomosis duodenal-ileal bypass with sleeve gastrectomy (SADI-S) are technically demanding hypo-absorptive bariatric procedures generally indicated in super-obese patients (BMI ≥ 50 kg/m2). Data from the literature prove the procedure to be safe and effective, with promising bariatric and metabolic effects. Anyway, international societies support the creation of multicentric national and international registries to obtain more ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…Single Anastomosis Duodenal-ileostomy with Sleeve gastrectomy (SADI-S) is a novel surgical technique, emerging from the BDPDDS legacy, aiming to reduce BPDDS risks, while maintaining its efficacy as one of the most effective interventions. It is considered a valid alternative to BPDDS, associated with a lower complication rate ( 25 ). It has also usually been considered an alternative to one-anastomosis gastric bypass (OAGB), more challenging from a technical point of view, but associated with a lower risk of complications.…”
Section: Primary Proceduresmentioning
confidence: 99%
“…Single Anastomosis Duodenal-ileostomy with Sleeve gastrectomy (SADI-S) is a novel surgical technique, emerging from the BDPDDS legacy, aiming to reduce BPDDS risks, while maintaining its efficacy as one of the most effective interventions. It is considered a valid alternative to BPDDS, associated with a lower complication rate ( 25 ). It has also usually been considered an alternative to one-anastomosis gastric bypass (OAGB), more challenging from a technical point of view, but associated with a lower risk of complications.…”
Section: Primary Proceduresmentioning
confidence: 99%
“…In this study, we present the results of our SADIS’ experience in an Italian high-volume bariatric center in terms of the outcomes of different surgical approaches. We performed the first SADIS’ case in July 2016, which was a robotic SADI-S, whereas the first laparoscopic SADI-S and the first laparoscopic SADI were performed in February 2017 and the only robotic SADI was performed in March 2021 [ 50 ]. Overall, the outcomes of 116 patients were reported.…”
Section: Discussionmentioning
confidence: 99%
“…A standardized postoperative protocol tailored to bariatric patients was used [ 10 , 12 ]. The severity of postoperative complications was graded according to the Clavien-Dindo classification [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, recent meta-analyses showed that, although it is a safe and efficient procedure, the range of results obtained is very wide [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%